Plotinus, Proclus and the Arabic Neoplatonism - Sousa, Meline Costa (Revista Archai, 2025)
In this article, I present a historiographical debate about the Arabic Neoplatonism from some assumptions since the 19th century. From the editions of the works and the posterior studies, the distinction between the Plotinian corpus in Arabic, the Plotiniana Arabica, and the Proclean corpus, the Procleana Arabica, was consolidated, given the way in which the relationship between the texts originally written in Arabic and their Greek sources was understood. However, in view of recent studies, different assumptions and methodologies have been adopted. Given the complexity of the discussion, in this text I will restrict myself to the analysis of two works originally written in Arabic, namely The Theology of Aristotle and the Discourse on the Pure Good, known as Liber de Causis. Starting from the critique of two traditionally accepted historiographical assumptions, the aim of the following analysis is to discuss how new approaches allow us a more unified understanding of the nature of the Arabic Neoplatonic corpus. A consequence of the distinction between the Plotiniana Arabica and the Procleana Arabica is to lock the texts into philosophical models that are different from these one found in the works themselves.